Primary Care Screening and Treatment for Latent Tuberculosis Infection in Adults - Muhammad Ilman, Muhammad Ilman; Suci Indriani, Suci Indriani (International Medical Journal Corp. Ltd, 2024)
Background: The literature on primary care screening and treatment for latent tuberculosis infection (LTBI) in adults reveals a multifaceted approach to addressing this public health issue. The foundational work by (Hirsch-Moverman, 2011) emphasizes the importance of treatment adherence, identifying factors that influence completion rates, which is essential for effective interventions. This early research sets the stage for ongoing studies that expand on strategies to improve LTBI management. Literature Review: The introduction of a novel primary care model by (Kunin et al., 2022) advocates for increased support for primary care clinics, emphasizing the role of dedicated staff in enhancing patient education and adherence to treatment. This model is crucial for improving overall effectiveness in managing LTBI within primary care. Qualitative research by (Thorburn Gray et al., 2022) highlights barriers faced by under-served populations in the UK, revealing significant gaps in systematic screening practices. This underscores the need for tailored approaches that address unique challenges and align with WHO recommendations for global screening efforts. Conclusion: In conclusion, the literature collectively underscores the importance of targeted interventions, adherence strategies, and the critical role of primary care providers in managing LTBI. Ongoing research and the implementation of evidence-based practices are essential for enhancing the effectiveness of screening and treatment efforts, ultimately contributing to the reduction of TB incidence.